POTENSI KULIT BUAH MANGGIS (Garcinia mangostana L) YANG DICAMPUR DALAM PAKAN UNTUK MENINGKATKAN KETAHANAN TUBUH DAN KELULUSHIDUPAN IKAN LELE DUMBO (Clarias gariepinus) TERHADAP PENYAKIT Motile Aeromonas Septicemia - Iesje Lukistyowati; Mario Syatma (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research was conducted on 12th May until 23rd July 2015 held at Parasite and Fish Disease Laboratory. The aims of this research was to determine the potency of mangosteen pericarp (G. mangostana L.) in feed to increase immunity of African catfish (C. gariepinus) on Motile Aeromonas Septicemia disease seen from the hematology parameters. The treatments were addition of mangosteen pericarp in feed with different concentration i.e : Kn (without mangosteen pericarp), Kp (without mangosteen pericarp and injected using A. hydrophila), P1 (addition mangosteen pericarp 2 g/kg of feed and injected using A. hydrophila), P2 (addition mangosteen pericarp 4 g/kg of feed and injected using A. hydrophila) and P3 (addition mangosteen pericarp 6 g/kg of feed and injected using A. hydrophila). Fish were maintained for 60 days. After 60 days treatment the fish were intramuscularly infected with A. hydrophila with density of 107cell/ml in a dose of 0,1 ml/fish. The best results showed that addition mangosteen pericarp in P3 treatment after challenged with A. hydrophila significantly different on haematocrit levels (22,94%), total leukocytes (104,83×103 cells/mm3), phagocytic activity (64,80%), and survival rate (100%). Total eritrocytes were not different significantly between treatment with 2,04×106 cells/mm3.